Effects of heat stress on the liver of the Chinese giant salamander Andrias davidianus: Histopathological changes and expression characterization of Nrf2-mediated antioxidant pathway genes. (August 2018) - Wang, Cong; Zhou, Yi-Lian; Zhu, Qi-Hui; Zhou, Zhong-Kai; Gu, Wen-Bin; Liu, Ze-Peng; Wang, Lan-Zhi; Shu, Miao-An
Abstract: Nuclear factor E2-related factor 2 (Nrf2) is a crucial transcription factor that regulates the basal and inducible expression of many antioxidant-relevant genes, and the Nrf2-mediated antioxidant pathway has been regarded as a critical switch in the initiation of cellular defence systems against oxidative damages. In this study, Nrf2 was first identified and characterized in the Chinese giant salamander ( Andrias davidianus ). A. davidianus was exposed to a high ambient temperature of 30 °C for various periods of time (0, 3, 6, 12, 24, 48 and 72 h). We investigated the effects of heat stress on alterations of the hepatic malondialdehyde (MDA) concentration, the activities of lactic acid dehydrogenase (LDH), catalase (CAT), glutathione peroxidase (GPx) and superoxide dismutase (SOD), the histology of the liver, and the mRNA expression patterns of 11 genes involved in the Nrf2-mediated antioxidant pathway in A. davidianus . The results showed that both the hepatic LDH activity and MDA content significantly increased after heat exposure, indicating that heat stress could induce cell injury and oxidative damage. Histological analysis of the liver showed that heat stress caused hepatocyte abnormalities, fat accumulation and ultrastructural alterations of the hepatocytes, endoplasmic reticulum and nuclei. The expression patterns of genes involved in the Nrf2-mediated antioxidant pathway in the liver were distinct when A. davidianus was exposed to heat stress. To the best of our knowledge, this study is the first on the characterization of Nrf2 in A. davidianus and even in amphibians. The results indicated that heat stress could induce oxidative damage, and the Nrf2 antioxidant pathway might play a critical role in the resistance against heat stress in A. davidianus . These findings will deepen and enrich the current knowledge on the evolutionary conserved antioxidant roles and mechanisms of Nrf2 in A. davidianus, or even in amphibians, in the antioxidant defence against heat stress. Highlights: Nrf2 was firstly identified and characterized in Andrias davidianus . Heat exposure caused oxidative damages and altered the ultrastructure of liver cell. Heat stress activated Nrf2-mediated antioxidant pathway in Andrias davidianus .